Application of Eco-Friendly MnFe2O4/TiO2 Nanocomposites for the Photocatalytic Degradation of Methylene Blue - Rahardian, Renaldy Baptista; Sari, Emi Kurnia; Istiqomah, Nurul Imani; Suharyadi, Edi; Wibowo, Nur Aji (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2024)
Methylene blue (MB) is a dye commonly utilized in the textile sector. Methylene Blue is an organic compound that readily dissolves in water, facilitating its transport with industrial liquid waste. Due to its non-biodegradable nature, it causes environmental pollution, especially in water sources. The study simulates industrial dye degradation using the green-synthesized MnFe2O4/TiO2 nanocomposites with Moringa Oleifera extract, using varying mass masses for photocatalytic tests. The co-precipitation method was employed to produce magnetic nanoparticles at the nanoscale. X-ray diffraction (XRD) analysis showed a crystalline size of 13.3 nm, while the Fourier Transform Infrared (FTIR) spectroscopy validated the existence of Mn-O, Fe-O, and Ti-O functional groups at wave numbers of 439.1 cm-1, 587.1 cm-1, and 586.8 cm-1, respectively, confirming the successful synthesis of the MnFe2O4/TiO2 nanocomposite. The band gap of the nanocomposite was determined to be 2.9 eV. Using UV light, the photocatalytic process successfully degraded the methylene blue, achieving a 99.9% reduction within 20 minutes, with the optimal mass being 0.02 grams. Additionally, the MnFe2O4/TiO2 nanocomposite demonstrated reusability due to its ease of separation from the reaction solution.